Philosophical-Critical Rethinking of the Conceptual Formulation of International Phenomena: The Study of Immigration and Refugees - Ali Esmaeili Ardakani (رهیافتهای سیاسی و بین المللی)
The main claim of the present study is that understanding the dynamics of international phenomena necessitates paying attention to concepts. In addition to their conceptual, cognitive and logical aspects, concepts also have a non-cognitive and supra-conscious facet. In other words, concepts are alive and interrelated. Therefore, denying the dynamics of concepts in human sciences and considering them merely as a tool with a cognitive function for understanding the real world without considering their other aspects may prevent researchers of international relations from acquiring a thorough understanding of this field and the analysis of its dynamics. This is highlighted further when concepts such as immigration, borders, nation-states, nationality, and the identity of the European Union, all of which play a key role in this study, are focused on one or more important issues in international relations. These issues, in addition to their cognitive aspects, will also affect the other facets of this field of study such as policy-making and decision-making. To illustrate the importance of this, immigration and asylum seeking as major global issues and part of the new agenda in international relations have been considered as the subject matter for this thesis. This has created challenges in explaining, understanding and analyzing existing approaches and theories in international relations, so much, so that while this changing identity displays the explanatory/analytical limitations of existing theories, it also makes it inevitable to apply new theoretical and conceptual approaches to understanding and elucidating the changing nature of these issues and their outcome. Hence, this Research sets out the shaping of a kind of conceptualization in international relations as its theoretical objective.